INOVASI PENUNTUN PRAKTIKUM BERBASIS GREEN CHEMISTRY PADA MATERI ELEKTROKIMIA - Fajriati, Putri; Yusbarina, Yusbarina; Fatisa, Yuni; Utami, Lisa (Journal of Chemistry Education and Integration, 2024)
AbstractThis research was instigated with inadequate laboratory facilities and no green chemistry based practical work guideline at school. This research aimed at finding out validity and practicality levels of green chemistry based practical work guideline on electrochemistry lesson that was designed. Design & development research (DDR) method was used in this research consisted of 4 steps—analysis, design, development, and evaluation. This research was conducted to the twelfth-grade students of MIPA at State Senior High School 1 Kampar. The research findings showed that the percentages of green chemistry based practical work guideline by media and material experts continuously were 95% and 96.43% with very valid criteria. The practicality percentages by chemistry subject teachers and student response continuously were 91.96% and 83% with very practical criteria. Based on these data, it could be concluded that green chemistry based practical work guideline was very valid and very practical to be used as a teaching material on electrochemistry lesson.Keywords : DDR, Practical Work Guideline, Green Chemistry, Electrochemistry